PENERAPAN PENDEKATAN SAINTIFIK BERBANTUAN KIT HIDROSTATIKA DAN PANAS PADA MATERI KALOR UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMAN 4 PEKANBARU - Ardiani, Rica; Azhar, Azhar; Zulhelmi, Zulhelmi (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This research aims to describe students' cognitive learning outcomes by applying the scientific approach assisted by KIT hydrostatics and heat in heat material and to determine the differences in students' cognitive learning outcomes between learning using the scientific approach assisted by KIT hydrostatics and conventional learning in heat material at SMAN 4 Pekambaru. The research method used is quasi-experimental with data collection techniques in the form of a posttest. This research uses a sampling technique, namely simple random sampling. The sample in this study included class XI Engineering 1 as the experimental class and class XI Engineering 3 as the control class. The analysis techniques used are descriptive analysis and inferential analysis. The results of research using descriptive analysis showed that the experimental class obtained an average cognitive learning outcome of 83.30 in the very high category, while the control class obtained an average cognitive learning outcome of 70.67 in the high category. The results of inferential analysis in hypothesis testing obtained a value of 0.000 with the condition p < 0.05, which means that there is a significant difference in student cognitive learning outcomes between classes that apply the scientific approach assisted by KIT hydrostatics and heat and classes that apply conventional learning on heat material.